Adjusting Beginning Reading Intervention Based on Student Performance: An Experimental Evaluation. (October 2013) - Coyne, Michael D.; Simmons, Deborah C.; Hagan-Burke, Shanna; Simmons, Leslie E.; Kwok, Oi-Man; Kim, Minjung; Fogarty, Melissa; Oslund, Eric L.; Taylor, Aaron B.; Capozzoli-Oldham, Ashley; Ware, Sharon; Little, Mary E.; et al.
This experimental study evaluated a model in which the delivery of a supplemental beginning reading intervention was adjusted based on student performance. Kindergarten students identified as at risk for reading difficulties were assigned to one of two versions of the Early Reading Intervention (ERI; Pearson/Scott Foresman, 2004). Students assigned to the experimental condition received the intervention with systematic adjustments based on student performance. Students in the comparison condition received the same intervention without instructional modifications. The experimental group outperformed the comparison group on all posttest measures at the end of kindergarten. Follow-up analyses at the end of first grade revealed a continued advantage for the experimental group. Findings suggest that systematically adjusting intervention support in response to student performance may be feasible and efficacious.